1997
DOI: 10.1007/pl00012270
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for Pulmonary Tuberculosis

Abstract: During the period 1990 -1994 a total of 578 operations were performed in 502 patients with various forms of tuberculosis. Most of the patients (68%) were men aged 20 to 50 years (70%). Sputum cultures were positive in 55% of the patients. More than half of all patients were chronic smokers, and about 10% were alcoholics or drug addicts. There were no human immunodeficiency virus-infected patients, and none with acquired immunodeficiency syndrome. The most frequent surgical interventions were, according to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
10

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 25 publications
(23 reference statements)
0
17
0
10
Order By: Relevance
“…In the cohort of patients with verified chronic pulmonary TB infection, the clinical form of TB was diagnosed as either cavitary TB (Ͼ3-cm cavern with a fibrotic capsule formed; n ϭ 10) or noncavitary TB (multiple tuberculomas or infiltrative TB; n ϭ 9) ( Table 1). Cavitary TB was considered to include extensive tissue destruction with formation of a fibrotic cavern, whereas noncavitary TB included limited fibrotic processes (44). In situ imaging of cryopreserved tissue sections was performed with lung biopsies from the TB lesions, as well as from the macroscopically normal distal lung parenchyma.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the cohort of patients with verified chronic pulmonary TB infection, the clinical form of TB was diagnosed as either cavitary TB (Ͼ3-cm cavern with a fibrotic capsule formed; n ϭ 10) or noncavitary TB (multiple tuberculomas or infiltrative TB; n ϭ 9) ( Table 1). Cavitary TB was considered to include extensive tissue destruction with formation of a fibrotic cavern, whereas noncavitary TB included limited fibrotic processes (44). In situ imaging of cryopreserved tissue sections was performed with lung biopsies from the TB lesions, as well as from the macroscopically normal distal lung parenchyma.…”
Section: Resultsmentioning
confidence: 99%
“…Surgical treatment of TB in Russia is performed when the patient fails to respond to conventional treatment with first-and/or second-line drugs due to irregular use of anti-TB drugs and/or development of multidrug-resistant TB. In Russia, excessively long treatment with anti-TB drugs is generally not recommended, and therefore patients with multiple caverns or tuberculomas who cannot be efficiently cured by means of chemotherapy are often given surgical treatment (44). Upon thoracic surgery, areas of damaged and fibrotic tissue are removed in order to decrease the mycobacterial load and thus prevent disease progression.…”
Section: Methodsmentioning
confidence: 99%
“…These operative methods invariably present some risk to the patient, and patients suffer cosmetic defects in the postoperative period. 19 A significant number of patients consequently refuse surgical management. Minimally invasive and/or drug-free treatment methods are therefore being investigated to explore options for complementary therapy methods to improve treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In 1997, Perelman et al (19) reported 161 surgical pulmonary tuberculoma cases. The choice of operation, wedge or lobectomy, was dependent on the anatomy of the tuberculoma.…”
Section: Surgical Treatment Of Pulmonary Tuberculomamentioning
confidence: 99%